BSSAnalyzer: a framework for analyzing and comparing bike-sharing systems - Iamato, Gabriel Campanelli; Souza, Higor Amario de; Kon, Fabio (Anais do Workshop de Computação Urbana (CoUrb); 2026: Anais do X Workshop de Computação UrbanaDO - 10.5753/courb.2026.22978, 2026)
Bike-sharing systems (BSS) are a valuable public infrastructure for sustainable mobility. Understanding how BSS is used may provide insights for urban planning and for the expansion of these systems. This work proposes BSSAnalyzer, an open-source object-oriented framework that integrates and analyzes data from cycling infrastructure, public transportation, points of interest (POI), and other urban features to evaluate BSS performance. We applied the BSSAnalyzer in cities of London, New York, and São Paulo. The results indicate strong correlations between BSS usage and POIs related to food, services, and commercial establishments. BSSAnalyzer can also highlight areas of higher public interest, key urban connectivity infrastructure, connectivity between neighboring BSS stations, inactive stations, and cyclist flow patterns.